After Adong: The Emerging Doctrine Of Native Title In Malaysia - Crook, Peter (Journal of Malaysian and Comparative Law, 2019)
Adong bin Kuwau & Ors v Kerajaan Negeri Johor & Anor established the concept of native title in Malaysian law. The decision was quickly followed by two High Court decisions; Nor Anak Nyawai & Ors v Borneo Pulp Planation Sdn Bhd & Ors, a case involving the logging of Iban forest land in Bintulu, Sarawak, and Sagong bin Tasi & Ors v Kerajaan Negeri Selangor & Ors, a case involving the taking of Temuan land in Sepang in injunction with the building of the Kuala Lumpur International Airport.